You can beat the "market": Estimating the return on investment for NHL team scouting - Schuckers, M. E.; Argeris, S. (Journal of Sports Analytics, 2015)
Scouting is a major part of talent acquisition for any professional sports team. In the National Hockey League (NHL), the `market` for scouting is set by the NHL`s Central Scouting Service which develops a ranking of draft eligible players. In addition to the Central Scouting rankings, NHL teams use their own internal scouting to augment their knowledge of eligible players and develop their own rankings. Using a novel statistical approach we show in this paper that the additional information possessed by teams provides better rankings than those of Central Scouting. Using data from the 1998 to 2002 NHL drafts, we estimate that the average yearly gain per team from their internal scouting is between $1.7MM and $5.2MM. These values are consistent across the three measures of player productivity that we consider: cumulative Games Played, cumulative Time On Ice and cumulative Goals Versus Threshold where we aggregate these metrics across the first seven years post draft. We used this time frame since teams generally retain rights to their draft picks for seven years. Further, we find that no individual team outperformed the others in terms of draft performance. Show less